Cerebrospinal Fluid Concentrations of Neuronal Proteins Are Reduced in Primary Angiitis of the Central Nervous System - Ruland, Tillmann; Wolbert, Jolien; Gottschalk, Michael G.; König, Simone; Schulte-Mecklenbeck, Andreas; Minnerup, Jens; Meuth, Sven G.; Groß, Catharina C.; Wiendl, Heinz; Meyer zu Hörste, Gerd (Frontiers in Neurology, 2018)
Primary angiitis of the central nervous system (PACNS) is a rare autoimmune vasculitis limited to the CNS often causing substantial disability. Understanding of this disease is impaired by the lack of available biomaterial. Here, we collected cerebrospinal fluid (CSF) from patients with PACNS and matched controls and performed unbiased proteomics profiling using ion mobility mass spectrometry to identify novel disease mechanisms and candidate biomarkers. We identified fourteen candidate proteins, including amyloid-beta A4 protein (APP), with reduced abundance in the CSF of PACNS patients and validated APP by Enzyme-linked Immunosorbent Assay in an extended cohort of patients with PACNS. Subsequent functional annotation surprisingly suggested neuronal pathology rather than immune activation in PACNS. Our study is the first to employ mass spectrometry to local immune reactions in PACNS and it identifies candidates such as APP with pathogenic relevance in PACNS to improve patient care in the future.